Pengembangan Wawasan Ekososioekopreneur Sebagai Upaya Peningkatan Kualitas Desa Mandiri - Darsono Darsono; Ratna Ani Lestari; Ali Achsan Mustafa (Indonesian Journal Publisher, 2023)
Samboggede Village, Merakurak District, Tuban Regency, East Java, is known as the pioneer of an independent village since 2018 with a Development Village Index (IDM) score in 2021 of 0.9497. In addition to maintaining the independent village category, efforts to improve the community's quality of life continue. Village officials and people involved in village development, such as Bumdes, tourism, and micro-small industries are the key and at the same time the driving force for improving the quality of life of village communities. There are 67 units of small micro industries including 50 units of household industries, including a village-owned enterprise and village tours. There are still 220 poor families out of 1,387 families, but this is more due to the motive of government assistance. Community service in the Political Science Masters Study Program, Wijaya Kusuma University, Surabaya is focused on developing eco-socio-eco-preneur insights, namely the introduction and deepening of modern entrepreneurship based on information and communication technology which includes (eco)-nomic, (socio)-cultural aspects, and (eco)-logy for plus village apparatus. Devotion focuses on developing eco-social-entrepreneurship insights in (1) improving the quality of the environment, socio-culture, and diversifying types of business (2) creating content for social media, which has been used institutionally directed at increasing village entrepreneurship personally-individually. Result of this assistance, people with existing smartphones can easily take advantage of their social media accounts and create attractive promotional content to share, so that the information can be reached as widely as possible. Apart from that, Samboggede Village as a village with business potential for its citizens and a natural tourism destination can continue to improve its status as an independent, progressive village.